Cyber Security for Children: Parental Monitoring from a Technological, Child Psychology and Islamic Psychospiritual Perspective during the Covid-19 Pandemic - Abdul Aziz, Nor Azah; Sa’ari, Che Zarrina; Wahab, Suzaily (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
Cyber ethics awareness and education is crucial when children surf the internet especially during the Covid-19 pandemic situations where internet use is a common norm. During the pandemic, children from preschool until secondary school level had to stay at home and learn online (Teaching and Learning at Home (PdPR)). In this study, interviews are conducted to parents on how children surf the internet during the pandemic and how parents monitor and advise their children. The findings of this research suggest that parental monitoring of children related to cyber issues is equally important for the children. Parents are noticeably given a lot of advice regarding the appropriate way of communicating when playing games, the types of games played by children, the commandments and prohibitions of Allah in Islam, and also the safety and health’s concern of children when playing games. Not only that, but parents also suggested to government agency such as Malaysian Communications and Multimedia Commission (MCMC) to increase regulation on those inapproproate websites in Malaysia and take proactive measures to prevent our personal data be misused by the cyber criminals such as scammers and pornorgraphy’s criminals. Proactive measures need to be taken by the government such as making restrictions on games like Mobile Legend because of the destructive effects it could have on the children’s behavior. Children who are negatively affected by the game will likely stay home most of the time and are reluctant to socialize. Besides, there are also other concerning safety issues raised by parents when children play games such as abusive words, bullies, games addiction and pornography